2020
DOI: 10.1080/08993408.2020.1832412
|View full text |Cite
|
Sign up to set email alerts
|

Computer science club for girls and boys – a survey study on gender differences

Abstract: Background and context: This study investigates differences in views of girl and boy members of a CS club. Objective:Understanding differences in the views of girls and boys regarding perceived parental attitudes and values, social support, appreciation of CS, and engagement in science and CS. Understanding differences in girls' and boys' view of CS, and future study and work aspirations related to science/CS.M Method: A survey was distributed to all members of a CS club. 115 boys and 39 girls aged 9-16 comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…However, we did not find explicit stereotypes for the statement that programmers like computers and have little other interests. No gender differences were found within this stereotype, which is in line with a study that found that both genders have similar associations to the word 'Computer Science' including the association 'game' [39]. The association of programming and video gaming might limit children who do not have an interest in video gaming to consider a career in IT.…”
Section: Interests Stereotypesupporting
confidence: 82%
“…However, we did not find explicit stereotypes for the statement that programmers like computers and have little other interests. No gender differences were found within this stereotype, which is in line with a study that found that both genders have similar associations to the word 'Computer Science' including the association 'game' [39]. The association of programming and video gaming might limit children who do not have an interest in video gaming to consider a career in IT.…”
Section: Interests Stereotypesupporting
confidence: 82%
“…In order to find out what the latest research has revealed about what keeps women from the IT field, a dozen review papers, published in the past two years, were selected. [9,10,11,12,13,14] After examining these recent papers, each dedicated to review the latest literature about young women's barriers, we can differentiate four basic obstacles that account for girls' scarcity in IT: social, selfefficacy, educational, and labour market factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most fundamental obstacle that girls face is gender stereotyping, that is, a binary world view that divides the social world into feminine vs. masculine domains and characteristics [15] connecting IT, and generally, STEM 1 to masculinity. [9,10,11,12,13,14] Gender-based social stereotypes can affect how young women's closest environment relates to their career interests, such as their families. It is especially fathers' and male siblings' attitudes that were shown to influence girls' choices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While initial enthusiasm for programming is essential, learning outcomes are equally important as they determine the resulting computing-related self-concept and perceived self-efficacy [41,47]. These are prerequisites for a longer-term interest in CS and whether learners consider themselves suitable for studies in CS.…”
Section: Introductionmentioning
confidence: 99%